Accurate Solution of Navigation Equations in GPS Receivers for Very High Velocities Using Pseudorange Measurements. (29th June 2014) - Rahemi, N.; Mosavi, M. R.; Abedi, A. A.; Mirzakuchaki, S.
Abstract : GPS is a satellite-based navigation system that is able to determine the exact position of objects on the Earth, sky, or space. By increasing the velocity of a moving object, the accuracy of positioning decreases; meanwhile, the calculation of the exact position in the movement by high velocities like airplane movement or very high velocities like satellite movement is so important. In this paper, seven methods for solving navigation equations in very high velocities using least squares method and its combination with the variance estimation methods for weighting observations based on their qualities are studied. Simulations on different data with different velocities from 100 m/s to 7000 m/s show that proposed method can improve the accuracy of positioning more than 50%.